Migraine and traumatic brain injury: a cohort study in Taiwan. Issue 7 (30th July 2019) - Wang, Qing-Rui; Lu, Ying-Yi; Su, Ying-Ju; Qin, Hao; Zhang, Li; Wu, Ming-Kung; Zhang, Cong-Liang; Wu, Chieh-Hsin
Abstract : Objective: Traumatic brain injury is now a major contributor to the global healthcare burden. Migraine is another debilitating disease with a global health impact. While most researchers agree that traumatic brain injury is a risk factor for migraine, whether migraine is a risk factor for traumatic brain injury still remains under debate. We therefore aimed to investigate whether migraine was a risk factor for developing traumatic brain injury. Study design: Retrospective population-based cohort study. Setting: Data for people who had been diagnosed with migraine were retrieved from Taiwan's National Health Insurance Research Database. Participants: We identified 7267 patients with newly diagnosed migraine during 1996–2010. The migraineurs to non-migraineurs ratio was set at 1:4 to enhance the power of statistical tests. Primary and secondary outcome measures: We used multivariate Cox proportional hazard regression models to assess the effects of migraines on the risk of traumatic brain injury after adjusting for potential confounders. Results: The overall traumatic brain injury risk was 1.78 times greater in the migraine group compared with the non-migraine group after controlling for covariates. Additionally, patients with previous diagnoses of alcohol-attributed disease, mental disorders and diabetes mellitus had a significantly higher traumatic brain injury risk compared with those with no history of these diagnoses. Conclusions: This study of a population-based database indicated that migraine is a traumatic brain injury risk factor. Greater attention to migraine-targeted treatment modalities may reduce traumatic brain injury-related morbidity and mortality.